209k views
3 votes
Identify the error in the student solution shown below. Find the correct answer.

Identify the error in the student solution shown below. Find the correct answer.-example-1
User Astrosyam
by
5.7k points

2 Answers

3 votes

\bf 2ln(x)=ln(3x)-[ln(9)-2ln(3)] \\\\\\ ln(x^2)=ln(3x)-[ln(9)-ln(3^2)] \\\\\\ ln(x^2)=ln(3x)-[ln(9)-ln(9)] \\\\\\ ln(x^2)=ln(3x)-\stackrel{\stackrel{\textit{it happened right here}}{\downarrow }}{\left[ \cfrac{ln(9)}{ln(9)} \right]} \\\\\\ ln(x^2)=ln(3x)-[1]\impliedby \textit{recall }(same)/(same)=1\\e 0
User Kairav Thakar
by
5.6k points
4 votes

The answer is Since 0 in ln(3x) - 0 is not a logarithm, the property of logarithms cannot be used here.

The difference shown cannot be written as a quotient of logarithms.

The step ln(x2) = ln(3x) - (0) reduces to

ln(x2) = ln(3x).

The possible solutions are 0 and 3, with 0 being extraneous.

User Elin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.